Determinants of Foreign Direct Investment in Six Fragile African Economies: Panel Data Modeling - Khattab, Ibrahim G.; Ebrahim, Ehab Ebrahim Mohamed; Ahmed , Awadelkarim Elamin Altahir; Albeltagy, Walaa Abdullah Abdullah (International Journal of Energy Economics and Policy, 2026)
Low-income African countries continue to face persistent political, economic, and environmental challenges that constrain their ability to attract foreign direct investment (FDI). Poverty, institutional weaknesses, and recurrent political instability have deterred investors and limited growth. While the relationship between macroeconomic indicators and FDI has been widely studied, existing research has largely focused on relatively stable regions such as Northern and Southern Africa, leaving fragile economies underexplored. This study addresses this gap by analyzing the determinants of FDI inflows in six low-income African countries over the period 2010–2023. Using annual panel data and panel regression models, the analysis reveals that past inflows of FDI exert a strong persistence effect. In addition, gross domestic product (GDP), inflation, and labor force are found to significantly and positively influence FDI, whereas trade shows no significant impact. These findings provide new insights into the determinants of FDI in fragile African economies and highlight important economic policy directions for enhancing investment attractiveness in these regions.